Study of synthesis, stability and thermo-physical properties of graphene nanoplatelet/platinum hybrid nanofluid - Yarmand, H.; Gharehkhani, S.; Shirazi, S.F.S.; Goodarzi, M.; Amiri, A.; Sarsam, W.S.; Alehashem, M.S.; Dahari, M.; Kazi, S.N. (Elsevier, 2016)
In the present study a new synthesis method has been introduced for the decoration of platinum (Pt) on the functionalized graphene nanoplatelet (GNP) and also highlighted the preparation method of nanofluids. GNP–Pt uniform nanocomposite was produced from a simple chemical reaction procedure, which included acid treatment for functionalization of GNP. The surface characterization was performed by various techniques such as XRD, FESEM and TEM. The effective thermal conductivity, density, viscosity, specific heat capacity and stability of functionalized GNP–Pt water based nanofluids were investigated in different instruments. The GNP–Pt hybrid nanofluids were prepared by dispersing the nanocomposite in base fluid without adding any surfactant. The examined nanofluids were stable and no significant sedimentation was observed for a long time (22 days). Thermal conductivity of GNP–Pt nanocomposite dispersed in distilled water nanofluids shows an enhancement of 17.77% at 40 °C and 0.1% weight concentration.